Naegeli-Franceschetti-Jadassohn syndrome: a systematic review of case studies - Shah, Hussain Haider; Hussain, Tooba; Subash, Arun; Qadir, Ramsha Abdul; Meshram, Yashika Rajesh; Shahzad, Maryam; Sultan, Wania; Hadi, Zeenat; Ashfaque, Faiza; Anas, Zahra; Rauf, Sameer Abdul; Waseem, Radeyah; et al. (Frontiers in Medicine, 2025)
IntroductionNaegeli-Franceschetti-Jadassohn syndrome (NFJS), also known as Naegeli Syndrome, is a rare autosomal dominant ectodermal dysplasia characterized by mutations in the KRT14 gene. These mutations disrupt ectodermal tissue development, leading to diverse clinical manifestations involving the skin, nails, teeth, and sweat glands.MethodologyA systematic search across PubMed, Google Scholar, European PMC, and Cochrane databases was conducted up to August 2023. Only case reports, case series, and original articles reporting cases were included.ResultsThis review incorporated 6 case reports, 2 case series, 3 original articles, and 1 editorials, encompassing 33 individuals diagnosed with NFJS. Key clinical features included extensive reticulate hyperpigmentation, palmoplantar keratoderma, and dental anomalies. Rarely reported findings, such as cerebellar fissures and generalized osteopenia, were noted in two cases. Treatment predominantly focused on symptomatic management using topical emollients and antioxidants.ConclusionNFJS remains a diagnostic challenge due to its rarity and overlap with other pigmentary disorders. This review consolidates current knowledge to aid clinicians in recognizing and managing NFJS. Further research is needed to clarify its pathogenesis and explore targeted treatments.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=447267, identifier CRD42023447267.